A prospective study on gestational diabetes mellitus in a tertiary care center - M., Poovathi; Devi, S. Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gestational Diabetes Mellitus is defined as any degree of glucose intolerance identified for the first-time during pregnancy. Gestational Diabetes Mellitus is a highly prevalent metabolic disorder among pregnant woman with rising incidence in recent years. Various risk factors are associated with this disorder leading to maternal and neonatal mortality. About 5% of the pregnancies are complicated by Gestational Diabetes Mellitus. The International Diabetes Federation estimates that one in six live birth (16.8%) are to women with some form of hyperglycemia in pregnancy. The prevalence of GDM in present study is 4.326%. Not only obesity but also overweight women have greatly increased risk of developing gestational diabetes. Methods: This includes study all cases of gestational diabetes mellitus admitted in the Department of Obstetrics, Government Mahatma Gandhi Memorial Hospital attached to K.A.P.V medical college, Trichy. This study has been conducted from January 2018 to June 2018.Fetal complications in infants born to diabetic mothers were studied. Maternal complications related to Gestational diabetes were also studied. Results: The total deliveries during this period were found to be 4085 of which 175 patients where diagnosed to have Gestational Diabetes Mellitus, thus the incidence accounts for 4.326%. The incidence in 20 to 25 years age group was around 67 which accounted for 37.3%. Most cases less than 20 years were found to be pregestational diabetes mellitus. The prevalence of GDM in present study is 4.326%. The maternal complications like vaginal infections accounted to 11.4%, gestational hypertension accounts to 14.3%, polyhydramnios to 17.1%. Regarding the fetal complications incidence of intrauterine death at term was around 8% and neonatal complications included hyperbiliribinemia 11.4%, hypoglycaemia, 6.7%, respiratory distress syndrome 5.75%. Conclusions: Gestational diabetes was associated with increased adverse maternal and perinatal outcomes.